Geotechnical problem solving - Lommler, John C. (Wiley, 2012)
"Devised with a focus on problem solving, Geotechnical Problem Solving bridges the gap between geotechnical and soil mechanics material covered in university Civil Engineering courses and the advanced topics required for practicing Civil, Structural and Geotechnical engineers. By giving newly qualified engineers the information needed to apply their extensive theoretical knowledge, and informing more established practitioners of the latest developments, this book enables readers to consider how to confidently approach problems having thought through the various options available. Where various competing solutions are proposed, the author systematically leads through each option, weighing up the benefits and drawbacks of each, to ensure the reader can approach and solve real-world problems in a similar manner The scope of material covered includes a range of geotechnical topics, such as soil classification, soil stresses and strength and soil self-weight settlement. Shallow and deep foundations are analyzed, including special articles on laterally loaded piles, retaining structures including MSE and Tieback walls, slope and trench stability for natural, cut and fill slopes, geotechnical uncertainty, and geotechnical LRFD (Load and Resistance Factor Design)"--